Preparation and characterization of poly (4- Vinyl Pyridine) grafted chitin beads - Oylum, Hasan (Eastern Mediterranean University (EMU), 2013)
ABSTRACT: The subject of this thesis is the preparation and characterization of chitin gel beads by thermoreversible gelation, which followed by nonsolvent addition, and via chemical modification followed by non-solvent addition. Physical properties of the chitin gels obtained by nonsolvent addition and by heating to the gelation point followed by nonsolvent addition were investigated. The effects of the type and composition of the solvent system on the gelation time, gelation temperature, swelling ratio and the Young’s modulus were studied. Another aspect of this study was to exploit the gel formation capability of chitin to form modified gel beads based on the polymer. To fulfill this aim, a new combined approach was taken to carry out redox initiated grafting under homogeneous conditions followed by nonsolvent addition to prepare poly(4-vinyl pyridine) (P4VP) grafted chitin gel beads. Grafting percentages up to 226% were obtained. The grafted and nongrafted products were characterized by FTIR spectrophotometry, XRD and SEM analyses and by TGA. The swelling behaviour of the beads was studied in aqueous solution in neutral, acid and phosphate buffers. XRD analysis showed that the characterized product had a lower crystallinity when compared to the pure chitin. Thermal analysis carried out by TGA revealed that the products were less stable against thermal treatment than chitin. While chitin had a weight loss of 75 % at 500ºC the grafted product showed 90 % weight loss. The maximum decomposition temperature for chitin was 380ºC, but for the grafted products this value was as low as 305ºC. The DSC analysis of the chitin and the grafted chitin confirmed less heat stability of chitin-g-P4VP. The potential of the gel beads for wastewater treatment applications was tested by studying their heavy metal and fat binding properties. The P4VP grafted and nongrafted gel beads were tested for their cholesterol and Fe3+ adsorption capacities. The beads derived from chitin-g-P4VP were found to have higher adsorption capacities than chitin beads due to a microporous bead surface and chemical modification. The quaternized chitin-g-P4VP gel bead proved to be a potential Hg2+ adsorbent. ………………………………………………………………………………………………………………………………………………………………………………………………………… ÖZ: Bu tezin konusu; kitin jel boncukların ısıl tersinir jelleşme, ısıl tersinir jelleşme işlemi sonrasında çöktürücü eklenmesi ve kimyasal modifikasyon sonrasında çöktürücü eklenmesi yöntemleri ile hazırlanması ve karakterizasyonudur. Çöktürücü eklenerek ve jelleşme noktasına kadar ısıtıldıktan sonra çöktürücü eklenerek hazırlanan jellerin fiziksel özellikleri incelendi. Çöktürücü sistem türünün ve bileşiminin jelleşme zamanı, jelleşme sıcaklığı, şişme oranı ve esneklik katsayısı üzerinde etkileri incelendi. Bu çalışmanın diğer bir boyutu ise, kitinin jelleşme özelliklerinin, modifikasyon sonrası da kullanılarak modifiye kitin jel küreler hazırlanmasıdır. Bu amaçla, yeni bir yaklaşımla kimyasal modifikasyon ve jelleşme bir arada kullanılarak poly(4-vinil piridin) aşılanmış kitin jel küreler hazırlanmıştır. En fazla 226% aşılanma yüzdesine ulaşılmıştır. Aşılanmış ve aşılanmamış ürünler FTIR spektrofotometresi, XRD, SEM ve TGA yöntemleri ile karakterize edildi. Kürelerin şişme davranışları sulu ortamda çalışılmıştır. XRD analizi, ürünlerin kitine göre daha düşük kristallik oranına sahip olduğunu göstermiştir. Kitin-g-(poli(4-vinil piridin)) kürelerin termal özellikleri ise TGA ile belirlenmiştir. Aşılanmış ürünlerin kitine göre ısıl kararlılıklarının daha düşük olduğu gözlemlenmiştir. 500˚C civarında kitin, %75 ağırlık kaybına uğrarken, aşılanmış kitinde bu oran %90 civarındadır. Normal kitinin maksimum bozunma sıcaklığı 380˚C iken, aşılanmış kitin için bu sıcaklık 305˚C’dir. Kitin ve aşılanmış kitinin DSC analizi, aşılanmış kitinin ısıl kararlılığının daha düşük olduğunu desteklemektedir. Potansiyel olarak jel kürelerin atıksu arıtım sistemlerinde kullanılabilirliğini test etme amaçlı olarak; metal ve yağ tutuculuk özellikleri üzerinde çalışılmıştır. Bu amaçla kitin-g-P4VP boncukların Fe3+ ve kolesterol tutuculuk kapasiteleri de incelenmiş ve aşılanmış boncukların aşılanmamış boncuklara göre daha fazla tutuculuk kapasitelerine sahip olduğu gözlemlenmiştir. Bunun sebebi ise aşılanmış kitin boncukların mikrogözenekli bir yapıya sahip olması ve kimyasal modifikasyona uğratılmış olmasıdır. Deneysel çalışmalar, kloroasetamid fonksiyonlu kuaterner kitin-g-P4VP kürelerin, Hg2+ iyonu yüzey tutuculuk uygulamaları için potansiyel olduğunu göstermiştir.
Doctor of Philosophy in Chemistry. Thesis (Ph.D.)--Eastern Mediterranean University, Faculty of Arts and Sciences, Dept. of Chemistry, 2013. Supervisor: Prof. Dr. Elvan Yılmaz.
Keywords: Toxicological Chemistry; Bioadsorbent - Biopolymer - Chitin - Chitosan - Poly (4-Vinyl Pyridine) - Grafting - Cholesterol - Heavy Metals - Iron - Mercury - Chitin Beads - Thermoreversible - Gelation - Quaternized Chitin